Pengaruh Suhu Pengeringan terhadap Struktur Amorf dan Sifat Fisik Nira Kelapa Serbuk dengan Penambahan Maltodeksrin - Ramanda, Muhammad Rizky (Communication in Food Science and Technology, 2023)
Sources of sucrose or food with high sugar content in Indonesia is sap/nira. Processed innovations from coconut sap besides brown sugar, can be made into powdered sugar. Powdered sugar can be crystalline or amorphous. One of the advantages of amorphous structures in high sugar products is the bright color and more soluble in water. Amorphous powdered coconut sugar in its manufacture has constraints, one of which is stickiness. This is because coconut sap is a food ingredient with high sugar content and has a low glass transition temperature of around 62°C, so it is necessary to add maltodextrin with a Tg value of 135-140°C to increase the value of the product's glass transition. In addition, the impact of the drying rate will affect the resulting structure. This research focuses on testing coconut sap powder with the addition of maltodextrin with a temperature comparison during the drying process. Where the temperature used is 50°C, 60°C, 70°C, 80°C using a vacuum dryer. Data analysis was carried out, namely the amorphous-crystalline structure test, hygroscopicity rate test and color test. The resulting data shows that the higher the temperature used, the higher the amorphous structure that is formed, and also has an impact on the hygroscopicity rate and color intensity.